(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate and determine the optimal conditions for the expression of active recombinant human monoamine oxidase B (MAO-B) in Pichia pastoris KM71. Methods: The P. pastoris KM71 strain carrying the gene encoding human MAO-B was used. Cultivation and induction conditions were investigated, including biomass-generating media (BMG, BMGY), induction media (BMM, BMMY), methanol concentrations (0.25%, 0.5%, 1%), and induction times (24 - 144 hours). Cell disruption conditions by mechanical bead beating were also optimized. MAO-B was purified by ion-exchange chromatography (HiTrap Q FF), and its activity was determined spectrophotometrically using benzylamine as a substrate. Results: The minimal medium BMG - BMM yielded higher enzyme activity than the complex medium BMGY - BMMY. A methanol concentration of 0.5% and an induction time of 24 hours resulted in the highest MAO-B activity. The optimal cell disruption condition was 6 cycles of 6-minute beating and 10-minute incubation in ice bath. MAO-B was successfully purified, eluting mainly at 30% and 40% HIGH-QB concentrations, and the purified enzyme exhibited an activity of approximately 2977 U/L. Conclusion: The study successfully expressed active recombinant human MAO-B in P. pastoris KM71 and identified optimal conditions for the expression, cell disruption, and initial purification processes, providing a foundation for further applications.